2010
DOI: 10.1097/mjt.0b013e3181ba3320
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Challenges in Combined Apical Ballooning Syndrome and Acute Pulmonary Decompensation

Abstract: Apical ballooning syndrome (ABS) is increasingly diagnosed in critical care settings. Widespread application of echocardiography and cardiac enzyme testing has increased its recognition. Our experience of 4 subjects illustrates the association of ABS with a wide spectrum of acute pulmonary disorders seen in critical care settings. All had ABS proven by normal coronary angiogram and subsequent normalization of left ventricular dysfunction. Bronchospasm due to chronic obstructive pulmonary disease exacerbation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Mayo criteria for SC diagnosis requires coronary angiogram to confirm absence of culprit lesions that may account for the RWMA 7, 11. Our interest is in early non-invasive diagnosis of SC in the critically ill. We have reviewed the various etiologies of cardiac dysfunction in the critically ill 12 and highlighted management issues specific to the critically ill 13, 14. We routinely encounter potential SC in various ICU settings and have published our algorithm to definitively diagnose SC without catheterization 9 .…”
Section: Defining Scmentioning
confidence: 99%
“…Mayo criteria for SC diagnosis requires coronary angiogram to confirm absence of culprit lesions that may account for the RWMA 7, 11. Our interest is in early non-invasive diagnosis of SC in the critically ill. We have reviewed the various etiologies of cardiac dysfunction in the critically ill 12 and highlighted management issues specific to the critically ill 13, 14. We routinely encounter potential SC in various ICU settings and have published our algorithm to definitively diagnose SC without catheterization 9 .…”
Section: Defining Scmentioning
confidence: 99%
“…Takotsubo cardiomyopathy (TCM) associated with chronic obstructive pulmonary disease (COPD) is considered a subset of TCM, suggesting a dangerous liaison of the heart-lung axis [ 1 - 3 ]. Manfredini, et al reported a high prevalence of lung pathologies, including asthma, COPD, and pulmonary embolism in a retrospective analysis of patients suffering from TCM [ 2 ].…”
Section: Introductionmentioning
confidence: 99%